Pengaruh Psikoedukasi tentang Bullying terhadap Munculnya Empati pada Siswa Kelas VI MIM Gonilan - Basmalah, Mutiara; Ibriza, Falihatul; Syahrani, Mutiara Sukma; Rhomadona, Dhevi Rizky; Sriwulandari, Kartika; Raihana, Ashfi (Universitas Muhammadiyah Metro, 2024)
The rise in cases of bullying committed by students has a detrimental impact not only on the victims but also on the perpetrators. This impact is not only felt during the period when bullying behavior occurs but can continue until the perpetrator and victim enter adulthood. This bullying problem must be addressed in several ways, one of which is psychoeducation. This research aims to determine the effect of providing information about bullying on the emergence of empathy in class VI students at MIM Gonilan. The method used in this research is a quantitative experimental one-group pre-and post-test design. The sample in this study was 47 class VI students at MIM Gonilan. After being given the material, students were given a pre-test and post-test to determine the level of student empathy in cases of bullying. The results of the analysis show the value of Asymp. Sig. (2-tailed) is 0.004 <0.05, indicating a significant difference between the pre-test and post-test. This shows the importance of providing bullying material and each student's empathy.